The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1413-86702008000500018
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia with Col-S strains: a successful comeback of colistin!

Abstract: Emergence of multi and pan-drug resistant Gram-negative bacteria causing nosocomial infections in intensive care settings has become a challenge for clinicians. The mortality rate of ventilator-associated pneumonia (VAP) is known to increase when the initial microbiological diagnosis and antimicrobial therapy are inappropriate. We present a case of a 18-year-old man, who after being admitted following an accident, had developed VAP due to multidrug resistant Pseudomonas aeruginosa and Acinetobacter spp. and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The antibiotics administrated, meropenem and colistin, were proven to be an efficient treatment strategy, managing to intercept the progress of a severe respiratory infection in a critically ill patient, in accordance to the literature [5, 6]. In addition, CT-guided drainage of the lung abscess, which followed in sequence, appeared to be an effective method to treat a lung abscess that was refractory to conventional therapy.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The antibiotics administrated, meropenem and colistin, were proven to be an efficient treatment strategy, managing to intercept the progress of a severe respiratory infection in a critically ill patient, in accordance to the literature [5, 6]. In addition, CT-guided drainage of the lung abscess, which followed in sequence, appeared to be an effective method to treat a lung abscess that was refractory to conventional therapy.…”
Section: Discussionmentioning
confidence: 64%
“…The development of lung abscesses in VAP are rare complications, particularly coming to the presence of acinetobacter baumanii, with almost complete lack of similar case reports, whose rarity could be attributed to the extensive use of broad-spectrum antibiotics in these patients [5]. …”
Section: Discussionmentioning
confidence: 99%
“…Some case reports indicated that intravenous colistin was effective and tolerable in children infected by A. baumannii (99,(101)(102)(103). It's has been reported in several trials that colistin is effective in the treatment of severe nosocomial infections caused by MDR Gramnegative bacteria and is generally well tolerated in pediatric patients, even after relatively long-term use (21,22).…”
Section: Use In Children: Also Seemed To Be Safe and Effectivementioning
confidence: 99%
“…Furthermore, surveillance studies have shown a high prevalence of reduced susceptibility for carbapenems, with resistance percentages between 40 and 60 % (Cereda et al, 2011;Gales et al, 2011). These epidemiological studies motivated some medical centres to institute polymyxins as one of the empirical drugs of choice in the treatment of HAI (Mukhopadhyay et al, 2008). Tigecycline emerged as an alternative drug for CRAB infections.…”
Section: Monotherapy For Acinetobactermentioning
confidence: 99%